Spectrum of acute kidney injury in obstetrics - Kaur, Amandeep; Chopra, Seema; Suri, Vanita; Kohli, Harbir Singh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Acute kidney injury (AKI) associated with pregnancy is a serious medical complication which can lead to significant maternal as well as perinatal morbidity and mortality. Methods: Forty antenatal/postnatal /postabortal patients who fulfilled the Acute kidney injury network criteria were enrolled and followed up till 3 months of acute insult/ postpartum. Results: Majority of the patients, 23/40(57.5%) with AKI presented in postpartum period, 14/40(35%) developed AKI in antenatal period and 3/40(7.5%) were postabortal. AKI was attributable mostly to sepsis in 11/40(27.5%) followed by hypertension and its complications which included eclampsia in 5/40(12.5%) and HELLP syndrome in 3/40(7.5%). 5/40(12.5%) patients had postpartum haemorrhage and abruptio placentae was found in 2/40(5%). Renal replacement therapy (RRT) was the treatment in majority of them 28(70%). 25/40(62.5%) had complete recovery of their renal functions whereas maternal mortality was seen in 10/40(25%) patients. Prolonged anuria was found to be highly significant in our study and served as poor prognostic factor towards maternal outcome (p=0.034). Out of 37 patients, 21(56.7%) had live births and 16 patients (43.2%) had still births. Conclusions: Timely initiation of RRT in patients with AKI associated with pregnancy has a good maternal outcome in the form of complete recovery of renal functions.